PS-BPC03-2: NIGHTTIME HOME BLOOD PRESSURE WAS ASSOCIATED WITH ADVERSE OUTCOMES IN SUBCLINICAL HEART FAILURE PATIENTS. (January 2023) - Komori, Takahiro; Hoshide, Satoshi; Kario, Kazuomi
Abstract : Objective: Nighttime blood pressure (BP) has stronger association with target organ damage and cardiovascular outcome than office BP, 24-hr BP, and awake BP in hypertensives. However, clinical significance of nocturnal BP, especially home nocturnal BP, was not established in heart failure (HF) patients. We hypothesized that nighttime home BP was associated with adverse outcome and investigated the association between nighttime home BP and the outcome in subclinical HF patients. Design and method: We analyzed 394 patients with NT-proBNP > 125pg/ml from a practitioner-based population with at least one cardiovascular risk factor who underwent home BP monitoring in the Japan Morning Surge-Home Blood Pressure study. Morning, evening and nighttime home BP were measured by validated, automatic, and oscillometric home BP devices, and cardiovascular events were followed up. Results: During a mean follow-up of 4.2 years, 43 cardiovascular events occurred. Morning home SBP, evening home SBP and nighttime home SBP were higher in event group than in non-event group (150 ± 23 vs 140 ± 17 mmHg, p = 0.01, 142 ± 22 vs 131 ± 16 mmHg, p < 0.01, 133 ± 22 vs 125 ± 17 mmHg, p < 0.01, respectively). In multivariate Cox regression analysis adjusting for significant variables, average of evening home SBP, and nighttime home SBP were significant predictors of the outcome (HR 1.02, 95%CI: 1.01–1.04, p = 0.01, HR 1.02, 95%CI: 1.01–1.04, p = 0.03, respectively). When nighttime home SBP of 120mmHg was used as cutoff, nighttime home SBP > 120mmHg was significantly associated with the outcome (HR 2.46, 95%CI 1.06–5.68, p = 0.04). Conclusions: Elevated nighttime home BP was significant predictor of cardiovascular outcomes in subclinical HF patients.